PEDAGOGICAL ASPECTS OF FORMATION OF HIGH UNIVERSAL HUMAN VALUES IN STUDENTS (American Journal of Interdisciplinary Research and Development, 2024)
This article focuses on the formation of the ability of students to understand, understand and compare high universal values, to understand international terms based on values, to demonstrate their competence in the organization of international pedagogical activities, in the effective organization of activities in the context of international cooperation.